SISTEM INFORMASI JASA FOTO COPY DAN PRINT SECARA ONLINE BERBASIS WEB - Ishak, Refindo (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Web-based online photocopy and print services are photocopy and print services that can be used via websites and smartphones and can be delivered by online motorcycle taxi services so that customers or service users do not need to come to the service place, in the process of developing a photo copy system and print is still manual, therefore the author wants to make a computerized online photocopy and print service. The WEB languages used are php and mysql as the database and uses the SDLC methodology by Dennis Barbara and Roberta (2012)